A need for the codification of the principle of good faith in Malaysia, particularly in consumer and commercial contract: a comparative study with United Kingdom and United States. / Ahmad Najmi Mohd Yusoff … [et al.] - Mohd Yusoff, Ahmad Najmi; Abdullah Suhaimi, Abdullah Azman; Saleh, Mohd Safwan; Aziz, Muhd Afiq Farhan (2013)
This research seeks to provide for a suggestion with regards to the codification of the principle of good faith in Malaysia. This research is conducted due to the fact that the recognition given by the Malaysian jurisdiction as to its application of good faith is only restricted to certain types of contract and thus, limiting its application. This research draws upon mostly primary sources including journals, articles, cases, books, legal reviews, interviews and many more. The other goal of this research is to address the effectiveness of the principle of good faith in providing remedies for the innocent parties in the event of a breach of contract. On the other hand, this research looks into the application, acceptance and enforcement of the principle of good faith in other jurisdictions by comparing the extent of application of good faith itself. By the end of the research, there will be a determination as to whether Malaysia needs to amend the existing statute which governs the contractual agreement by including the principle of good faith into its provision.